High precision measurements of the ground state hyperfine structure interval of muonium and of the muon magnetic moment - Liu, Wei; Jungmann, Klaus; Prigl, Ralf; Putlitz, Gisbert zu; Reinhard, Irene; Schwarz, Willi (Physical review letters, 1999)
High precision measurements of two Zeeman hyperfine transitions in the ground state of muonium in a strong magnetic field have been made at LAMPF using microwave magnetic resonance spectroscopy and a resonance line narrowing technique. These determine the most precise values of the ground state hyperfine structure interval of muonium Δν=4463302765(53)Hz (12ppb), and of the ratio of magnetic moments μμ/μp=3.18334513(39) (120ppb), representing a factor of 3 improvement. Values of the mass ratio mμ/me and the fine structure constant α are derived from these results.